Mobbing in Lithuania: Situation of the division and the organisation on the levels of individual statements - Vveinhardt, Jolita (Business: Theory and Practice, 2010)
The foreign and Lithuanian authors who analysed mobbing and discrimination phenomena are presented in the article. The criteria which form the characteristics of the research instrument (the features of mobbing as discrimination in employee relations; the actions of mobbing as discrimination in employee relations; additional features of mobbing as discrimination in employee relations) are discussed. Individual statements of the instrument, which signal about the strength of mobbing on the level of the division and/or the organisation, are distinguished.  Diagnosing the situation of the division and the organisation on the levels of individual statements was an integrate part of the research which aimed at determining the expression of mobbing as discrimination in employee relations in order to improve the climate of Lithuanian organisations. 1379 respondents, representing public and private sectors (private sector – 998 observations, public sector – 381 observations) participated in the research. Organisations of twenty-two fields of professional activities comprise the sample. The results of research of Western scientists, i.e. mobbing is comparatively more distinct in the fields of education, health care and social work, have been proved. However, the result revealed in Lithuanian organisations shows that mobbing phenomenon is common in the spheres of publishing, commerce, transport and agriculture. The results of the research in Lithuanian organisations show that mobbing is nevertheless more pronounced in private sector organisations. This could be associated with the competition. The public sector is characterised by a specific work structure and staff training, determining a limited choice of jobs. As a result of a relatively low supply, the labour market is limited and the workplace more valued. The results of the research confirmed the hypothesis that mobbing is the problem of the whole organisation.Article in Lithuanian.Mobingas Lietuvoje: padalinio ir organizacijos situacija pavienių teiginių lygmenimisSantrauka. Straipsnyje pristatomi užsienio ir Lietuvos autoriai, analizavę mobingo bei diskriminacijos reiškinius. Aptariamos tyrimo priemonės charakteristikas (mobingo kaip diskriminacijos darbuotojų santykiuose požymiai; mobingo kaip diskrimina-cijos darbuotojų santykiuose veiksmai; papildomi mobingo kaip diskriminacijos darbuotojų santykiuose požymiai) sudarantys kriterijai.  Išskiriami  pavieniai  priemonės  teiginiai,  nusakantys  mobingo  raiškos  stiprumą  padalinio  ir  (arba)  organizacijos lygmeniu.  Padalinio  ir  organizacijos  situacijos  diagnozavimas  pavienių  teiginių  lygmenimis  buvo  sudėtinė  tyrimo,  kuriuo siekta nustatyti mobingo kaip diskriminacijos darbuotojų santykiuose raišką, gerinant Lietuvos organizacijų klimatą, dalis. Apklausoje dalyvavo 1379 respondentai, atstovaujantys viešajam ir privačiam sektoriams (privatus sektorius – 998 stebiniai, viešasis sektorius – 381 stebinys). Į imtį pateko dvidešimt dviejų profesinės veiklos sričių organizacijos. Pasitvirtino Vakarų mokslininkų tyrimų rezultatai, t. y. mobingas kur kas ryškesnis švietimo bei sveikatos priežiūros ir socialinio darbo srityse. Lietuvos  organizacijose  išryškėjęs  rezultatas  –  mobingo  reiškinys  dažnas  leidybos,  prekybos  ir  transporto  bei  žemės  ūkio veiklos srityse. Tyrimo rezultatai Lietuvos organizacijose rodo, kad mobingas dažnesnis privataus sektoriaus organizacijose. Tai būtų galima sieti su konkurencija. Viešajam sektoriui būdinga savita darbo struktūra. Dėl palyginti mažos pasiūlos darbo rinka yra ribota, o dėl socialinių garantijų darbo vieta labiau saugoma. Tyrimo rezultatai patvirtino hipotezę, kad mobingas yra visos organizacijos problema.Reikšminiai žodžiai: mobingas, diskriminacija, darbuotojų santykiai, padalinys, organizacija.